Über den Einfluß von Temperatur- und Luftfeuchtigkeitsstufen auf die Entwicklungsgeschwindigkeit, den Nahrungsverbrauch und die Raupensterblichkeit des Goldafters, Euproctis chrysorrhoea L. (Lepidoptera). - Fankhänel, Heinz (Contributions to Entomology = Beiträge zur Entomologie, 1959)
The medium length of larval and pupal development studied under 9 combinations of degrees of different temperature and atmospheric humidity was found to become the shorter the higher the temperature was applied (med. length of development under 75% rel. humid, and 17°C: 51 days; 22,5°C:32 days; 28°C: 22 days). Alternating temperatures under field conditions favoured the progress of larval development more than 2°C higher constant temperatures in the laboratory. While the length of larval development was generally encreased by low degrees of humidity (45%) the pupae under these conditions could earlier finish their development. The daily consumption of a larva (measure: the medium superficies of an oak leaf) was found under 28°C and 75% rel. humid, after 3. moulting 1 cm2, after 4. moulting 3-4 cm2, and within the first days after 5. moulting 4,5-12,5 cm2. The whole leaf superficies required during its development was 60-70 cm2. Heavy damage to oak buds was observed (April-Mai 1954) when, caused by low night temperatures the unfolding of oak buds stagnates, and the larvae, stimulated by high day temperatures (more than 12°C), leave the hibernating nests at a time when their food is confined to the buds only. There is given a comparison between the phenology of Euproctis chrysorrhoea in Germany (river-meadow district of the Elbe) and notes on this subject from Krasnodar district (USSR).